2015
DOI: 10.1016/j.elecom.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically microporous polymer slows down fuel cell catalyst corrosion

Abstract: The limited stability of fuel cell cathode catalysts causes a significant loss of operational cell voltage with commercial Pt-based catalysts, which hinders the wider commercialization of fuel cell technologies. We demonstrate beneficial effects of a highly rigid and porous polymer of intrinsic microporosity (PIM-EA-TB with BET surface area 1027 m 2 g -1 ) in accelerated catalyst corrosion experiments. Porous films of PIM-EA-TB offer an effective protective matrix for the prevention of Pt/C catalyst corrosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…PIMs [23,24] provide a new generation of highly rigid microporous materials with (i) excellent processability, (ii) highly rigid pore structures in which guest catalyst molecules can be readily embedded, (iii) good access of solvent and substrate to the catalyst through rigid pores and (iv) robustness towards corrosion. In our previous work, the poly-amine structure PIM-EA-TB [25] (synthesised based on a Tröger's base reaction [26][27][28]) has been employed to electrochemically grow palladium lamellae [29], to act as a host for molecular Fe(II)-porphyrinato electrocatalyst [30] and to protect gold nanoparticles [31] and fuel cell catalysts [32]. Recently, we have demonstrated proof of concept for the immobilisation of the molecular electrocatalyst 4-benzoyloxy-TEMPO (or 4B-TEMPO) into a porous PIM-EA-TB host film for the electrocatalytic oxidation of saccharides [33].…”
Section: Introductionmentioning
confidence: 99%
“…PIMs [23,24] provide a new generation of highly rigid microporous materials with (i) excellent processability, (ii) highly rigid pore structures in which guest catalyst molecules can be readily embedded, (iii) good access of solvent and substrate to the catalyst through rigid pores and (iv) robustness towards corrosion. In our previous work, the poly-amine structure PIM-EA-TB [25] (synthesised based on a Tröger's base reaction [26][27][28]) has been employed to electrochemically grow palladium lamellae [29], to act as a host for molecular Fe(II)-porphyrinato electrocatalyst [30] and to protect gold nanoparticles [31] and fuel cell catalysts [32]. Recently, we have demonstrated proof of concept for the immobilisation of the molecular electrocatalyst 4-benzoyloxy-TEMPO (or 4B-TEMPO) into a porous PIM-EA-TB host film for the electrocatalytic oxidation of saccharides [33].…”
Section: Introductionmentioning
confidence: 99%
“…soluble in organic solvents for casting of films and membranes [17]) and highly porous with typical BET surface area values ≈1000 m 2 g -1 [18]. Initial work focused on the gas-phase, but recently also liquid-phase applications have been explored based on stabilisation of fuel cell catalysts [19], "heterogenisation" of molecular catalysts [20,21], formation of novel microporous heterocarbon structures [22], and current rectification [23]. In previous work we employed solution casting methods to give relatively thick (typically 10 m or more) PIM membranes.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, voltammetric responses for the silver microparticles are more stable and repeatable. Within the potential range studied here PIM-EA-TB has no direct electrochemical activity [13,14] and it can be considered both cation and anion conducting [15]. Generally, with the PIM-EA-TB coating applied features such as the position of oxidation and back-reduction voltammetric responses are maintained and also the complex peak shape observed during the reduction is retained.…”
Section: Resultsmentioning
confidence: 97%
“…It has been demonstrated that metal nanoparticle catalysts can be PIM-coated and thereby protected against poisoning [13] and against detrimental loss and corrosion processes [14]. Here, we employ an intrinsically microporous polymer (PIM) material based on an ethanoanthracene (EA) building block that was synthesised employing a Tröger base (TB) method (PIM-EA-TB [15], see molecular structure in Fig.…”
Section: Introductionmentioning
confidence: 99%